PENGUATAN KOMPETENSI GURU IPA MELALUI PELATIHAN PENGEMBANGAN SUMBER BELAJAR DAN ASESMEN BERBASIS BUDAYA LOKAL DI SUNGAI KAKAP - Hairida Hairida; Hery Kresnadi; Muhammad Irfan Izudin; Agung Hartoyo; Siti Halidjah; Kartono Kartono; Dyoty Auliya Vilda Ghasya; Asmayani Salimi; Rio Pranata; Nany Safrianty; Anggi Fatmadiwi; Rachmad Kurniawan; Siti Mariyam (Universitas Mataram, 2026)
This Community Service Program was motivated by the science learning practices in primary and secondary schools in Sungai Kakap District, which remain largely theoretical, rote-oriented, and insufficiently connected to local cultural contexts. Science teachers have not optimally utilized digital technology as a learning resource and an assessment tool. These conditions reduce the meaningfulness of science learning for students. Therefore, training focused on developing local culture-based learning resources and assessment was considered necessary. This program aimed to enhance the competencies of primary and secondary science teachers by developing culture-based learning resources and authentic assessment methods. The program was implemented through three stages: preparation, implementation, and monitoring and evaluation, using participatory methods such as discussion, demonstration, and hands-on practice. The activity was conducted on 31 August 2025, in Sungai Kakap District and involved 20 primary and secondary science teachers. Evaluation instruments included participant activity observation sheets, product assessment rubrics, and participant response questionnaires. Success indicators encompassed active participant engagement, the development of Sungai Kakap local culture-based learning resources and assessment, and positive participant responses to the program. The results indicated an improvement in teachers’ ability to integrate local culture into science learning. Approximately 80% of participants identified relevant local cultural potential and designed context-based performance tasks, while 60% successfully developed prototype e-supplements and simple video learning storyboards. Observations showed high levels of active participation and collaboration during the training. Questionnaire results indicated that participants perceived the program as relevant and applicable. Overall, this community service program effectively strengthened teachers’ pedagogical competence and digital literacy while promoting more contextually and meaningfully grounded science learning.